An adaptive, color based lane detection of a wearable jogging navigation system for visually impaired on less structured paths - Ramer, Christina; Seßner, Julian; Lichtenegger, Thomas; Landgraf, Maximilian; Franke, Jörg (2016 6th IEEE International Conference on Biomedical Robotics and Biomechatronics (BioRob), 2016)
Based on a previously published version of a first prototypic jogging navigation system for visually impaired and blind people, this paper presents an adaptive lane detection method that extents the use on standard running tracks to general and less structured paths. Additional and supporting developments refer to an active camera stabilization, the improved intuitive vibration feedback and the integrated and embedded mechatronic system setup.